2020
DOI: 10.47513/mmd.v12i2.679
|View full text |Cite
|
Sign up to set email alerts
|

Music Therapy for Chronic Fatigue Following Epstein-Barr Virus Infection in Adolescents

Abstract: This research study, which was a part of arandomized controlled trial, explored music therapy as a part of an individually tailored mental training programfor Chronic Fatigue(CF) following Epstein-Barr virus (EBV) infection in adolescents. This article presents the qualitative data stemming from the interviews, which focused on music therapy. The interviews were performed after completion of the program. The mental training program consisted of 10 sessions distributed between a family session (1), individual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Taken together, this suggests that the intervention was well tolerated, corroborating results from a recently published qualitative study which reported high levels of satisfaction among those that received the mental training programme. 40 We cannot rule out that the drop-out of six individuals in the intervention group before or immediately after startup of therapy was due to low tolerability in these participants. However, more probably, this loss to follow-up had the same cause as the poor recruitment of eligible patients into the study.…”
Section: Discussionmentioning
confidence: 95%
“…Taken together, this suggests that the intervention was well tolerated, corroborating results from a recently published qualitative study which reported high levels of satisfaction among those that received the mental training programme. 40 We cannot rule out that the drop-out of six individuals in the intervention group before or immediately after startup of therapy was due to low tolerability in these participants. However, more probably, this loss to follow-up had the same cause as the poor recruitment of eligible patients into the study.…”
Section: Discussionmentioning
confidence: 95%
“…Such is the case of cognitive-behavioral psychological treatment [ 3 , 4 , 32 ], mindfulness [ 33 , 34 , 35 , 36 , 37 ], guided imagery, and relaxation training [ 38 ]. Music therapy has also proven effective in treating different chronic diseases and their effects [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Music therapy comprises various models and methods [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%